“VERSES ON THE PASSION OF THE LORD” BY DYMYTRII TUPTALO - Savenko, Oksana (Літературний процес: методологія, імена, тенденції, 2019)
DOI: 10.28925/2412-2475.2019.1413 The article studies the “Verses on the Passion of the Lord” by the Ukrainian hagiographer and poet of the late 17th — early 18th centuries. Dimitrii Tuptal from the point of view of transformations in the work of the Easter plot. In these verses the poet reproduces the main events of the Easter cycle through allusions and reminiscences of the canonical Gospel text. The verses include repmarks of eleven “children” who speak about the cruel means of mockery of Jesus Christ at Calvary: a rope bound by Jesus, a warrior’s hand, a whip, a wooden pole to which Christ is tied, a crown of thorns , a cane, nails, a hammer that nailed Jesus to the cross, bile with vinegar, a spear that pierced Jesus’ ribs, and a deathbed. All these attributes of the “passions of Christ” are presented in the canonical Gospels, and Tuptalo focuses on them when the “children”, from the first to the eleventh, proclaim their monologues, each of which verbally reveals “their” attribute. The article compares the text of the verse with the corresponding places in the canonical Gospels and identifies the peculiarities of transformation in the verses by Dimitri Tuptal. The poet does not convey the “passion of Christ” but creatively elaborates the Gospel story.